Prevalence and associated factors of burnout among working adults in Southeast Asia: results from a public health assessment - Abdul Aziz, Amani Fadzlina; Ong, Tiffanie (Frontiers in Public Health, 2024)
The COVID-19 pandemic has spotlighted the mental health crisis among employees worldwide. However, burnout research is often industry- or occupation-specific, and limited knowledge currently exists on the prevalence of burnout in the general working population of Southeast Asia. This study aims to examine the prevalence of employee burnout and its associated factors among working adults in Southeast Asia using secondary data. 4,338 full-time employees aged 18–65 years old living in Malaysia, Singapore, Philippines, and Indonesia were assessed for burnout, depression, anxiety, stress, and sociodemographic characteristics as part of an online public health assessment in October 2022. The prevalence of burnout in the region was 62.91%. Burnout was highest among employees in the Philippines (70.71%) and lowest in Malaysia (58.13%). Experiencing burnout was associated with severe or extremely severe depression (AOR = 6.48 [95% CI = 5.06–8.33]), anxiety (AOR = 2.22 [1.74–2.85]), and stress (AOR = 5.51 [4.13–7.39]). Working more than 50 hours a week (AOR = 1.38 [1.04–1.82]) and being very dissatisfied with the job led to higher odds of burnout (AOR = 16.46 [8.99–30.53]). Alarmingly, more than half of working adults in the region are reporting increased levels of burnout, and improving employee mental health and work conditions may be key to improving employee burnout in the region. Findings contribute to existing research on burnout prevalence in the region and provide more comprehensive insights into understanding the factors driving employee burnout in the working population of Southeast Asia 2 years after the onset of the pandemic.